STUDENTS' REFLECTIVE ABSTRACTION LEVEL IN SOLVING MATHEMATICS PROBLEMS BASED ON COGNITIVE STYLES FIELD INDEPENDENT (FI) AND FIELD INDEPENDENT (FD) - Aning Wida Yanti; Yuni Arrifadah; Adelia Ayu Mustikarini (MATEMATIKA DAN PEMBELAJARAN, 2022)
Reflective abstraction is an activity to construct mathematical concepts through similarities and combinations of existing structures and reorganized into four levels: (1) recognition, (2) representation, (3) structural abstraction, and (4) structural awareness. Each individual has different characteristics of cognitive style in processing information. Differences in cognitive style affect the individual's ability to understand the problem. This study aims to describe students' level of reflective abstraction in solving mathematical problems in terms of field-independent (FI) and field-dependent (FD) cognitive styles. This research is a qualitative descriptive study. Task-based interviews carried out the data collection technique. The results are that field-independent (FI) students can correctly perform all levels of reflective abstraction in the stages of solving mathematical problems, but field-dependent (FD) students can only do abstraction on the introduction and representation.